Do herói as mentalidades: a questão do sujeito histórico para o ensino de história - Maria Inez Lemos Soares (1989)
Diferent cancepts of What is known as historical subject have influenced history teaching with the objetive os questioning history and its numerous versions. Actually, this essay focus differente concepts of what a historical subject is, as follows;burgeols concepts: liberalism, positivism and idealism, materialistic and dialectic concepts, structural and post-structural concepts and the New History's approach. Annales school and Mentalities.It has beome a necessity to bring to history teaching ways of showing how new historical subjects have gradually taken part in history in a much more efective and participative way.We cannot just go over our historical knowledge without questioning the participation level of different extrcts of our complex society. In fact, when we talk about social group's participation, we mean nothing but democracy. Indeed, this is what democracy is all about, a continuous search for social equality and the right to take part in decision-Making despite all social differences. Above all, this piece of work has as its main objective, to find a more rellable, truthful and up to date way of teaching history, taking into consideration new aspects of human life based on historical approaches such as: history of mentalities and New History. We hope we can this way, contribute to the development of society as well as to history. We hope we can this way, contribute to the development of society as well as to history theaching itself.